Therapeutic management of buying/shopping disorder: A systematic literature review and evidence-based recommendations - Vasiliu, Octavian (Frontiers in Psychiatry, 2022)
The prevalence of buying/shopping disorder (B/SD) has been increasing in the last two decades, and this disorder has a substantial negative impact on general functioning and quality of life. Therefore, a systematic review of the studies dedicated to the efficacy and tolerability of therapeutic interventions, both psychological and pharmacological, might help clinicians to decide on the most evidence-based treatment for these patients. In order to further increase the clinical usefulness of the current review, GRADE-based recommendations were formulated, where enough evidence was found to support such an approach. A number of five electronic databases were searched for single case reports, case series, open-label and double-blind, placebo/active intervention-controlled trials, but other secondary reports (i.e., systematic reviews and meta-analyses) were also included in this analysis. Studies with unspecified designs or those that do not report either qualitatively or quantitively the evolution of B/SD core manifestations were excluded. All data included in the secondary analysis were evaluated using the Joanna Briggs Institute critical appraisal checklists. A total number of 24 manuscripts (i.e., 12 clinical trials, eight case reports, and four reviews) were included. Most of the reviewed studies were of moderate quality, representing a certain limitation of this review and preventing the formulation of high-validity recommendations. Psychotherapy, especially cognitive behavioral therapy (CBT) seems to be the main intervention supported by the current evidence, followed by the combination of antidepressants and CBT, and serotoninergic antidepressants as monotherapy. There is an obvious need to further develop good-quality trials with a more significant number of participants with B/SD and longer follow-up periods.